CDT vs. GGT for the certification of the fitness to hold the driving license. A comparison based on the association of incremented values with the occurrence of alcohol-related road traffic accidents. (1st November 2021) - Porpiglia, Nadia M.; Bortolotti, Federica; Micciolo, Rocco; Canal, Luisa; Murari, Matilde; Gibelli, Filippo; Tagliaro, Franco
Abstract: Background: In the context of fitness certification to hold the driving license, GGT and CDT have been used, sometimes in combination (γ-CDT), to exclude chronic alcohol abuse. The present study was carried out with the aim of comparing the power of these biomarkers as tools for the objective screening of subjects at high risk of alcohol-associated traffic injuries. Methods: 288 male drivers admitted to hospital after traffic accidents were examined by determination of GGT, CDT and BAC. The degree of association of GGT, CDT and γ-CDT with BAC was analysed using non-parametric statistics. Results: Partitioning the cases using the cut-off concentrations of 0.5 g/L for BAC (the legal limit adopted in most European countries), 55 U/L for GGT and 1.9% for CDT, a highly significant difference was found between the frequency of elevated GGT or CDT in cases where BAC was within the legal limits and those with elevated BAC values (Fisher's exact test: p  < 0.001). However, the calculation of the odds ratio showed a much higher increase for CDT (28 times) than for GGT (6 times) in those drivers with a BAC above the Italian legal limit in comparison with those showing a BAC within the cut-off; conversely, γ-CDT does not provide any significant advantage vs. CDT alone. Conclusions: Both GGT and CDT provide objective evidence of an association with the occurrence of alcohol-related severe traffic accidents, but CDT shows superior association with these events. Therefore, CDT, notwithstanding higher costs, should be preferred in a forensic/certification context. Highlights: GGT, CDT and γ-CDT were compared as diagnostic tools in a certification context. Samples from traffic accidents were examined by determination of GGT, CDT and BAC. The degree of association of these biomarkers with BAC was studied. CDT provided a stronger association with the risk of traffic accidents vs. GGT. CDT, notwithstanding higher costs, should be preferred in forensic contexts.